Safety of Minimally Invasive Percutaneous Nephrolithotmy in High Risk Patients in Lateral Position - A Single Center Study - khizar, Samina; Nawaz, Muhammad; Farooq, Umer; Shehzad, Khubaib; Murtaza, Badar; Akmal, Muhammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the safety and efficacy of minimally invasive percutaneous nephrolithotomy with fluoroscopy aided renal access in the lateral position, in patients who were high-risk cases for anesthesia in prone position.Study Design: Prospective observational study.Place and Duration of Study: Armed forces institute of Urology, Rawalpindi, from Jan 2018 to Dec 2019.Methodology: Fifty-three patients with renal stones >1.8cm underwent minimally invasive percutaneous nephrolithotomy with fluoroscopy-guided renal access in the lateral position. All the patients were obese, some had severe ischemic heart disease, few had diabetes mellitus. All the patients were unfit for the prone position.Results: Successful renal access was achieved in all the patients (100%). The mean size of stone was 28 + 13.2 mm, with an average operative time being 55 ± 13.56 minutes and the mean hospital stay was 1.8 ± 2.3 days (range 2-4 days). No visceral or pleural injuries were documented. In addition, only two patients required postoperative transfusion. After procedure, the rate of complete stone clearance initially was 90.6%, which improved to 96% after single session of extracorporeal shockwave lithotripsy (ESWL). Only 2 (3.77%) patients had persistent residual stone fragment.Conclusion: Minimally invasive percutaneous nephrolithotomy with fluoroscopy-guided renal access in the lateral decubitus flank position, is safe and convenient in high-risk patients where prone position is contraindicated.